Nuclear Magnetic Resonance Studies of Borax, Tincalconite and Ferroelectric Lithium Hydrazinium Sulphate - Cuthbert, John David (My University, 1963)
The quadrupole coupling tensors at the B11 and Na23 sites in borax and tincalconite, two members of the hydrated sodium tetraborate family have been completely evaluated using broadline nuclear magnetic resonance (n.m.r.) techniques. The results have enabled deductions to be made concerning the crystal chemistry of boron, the coordinations of the sodium atoms and the crystallographic symmetries. Changes in the Li7 n.m.r. spectrum of ferroelectric lithium hydrazinium sulphate as a function of temperature were followed in detail. A previously undetected second order phase transition leading to a high temperature polymorph is complete at 164°C, The quadrupole coupling tensors at the Li7 sites have been completely evaluated in the two phases. The second moments or the proton n.m.r. spectrum from powdered lithium hydrazinium sulphate have been determined within the temperature range -183°C to 225°C, and single crystal data on the protons have been obtained at room temperature. It is shown that the nitrogen and hydrogen atoms exist in the structure as the hydrazinium ion NH2 and-NH3+. Detailed information is derived concerning the proton-proton vectors and the modes of reorientation of the NH2 and-NH3+ groups at various temperatures. Mechanisms for the ferro-electric switching at room temperature and for the transition to the high temperature polymorph are proposed on the basis of the experimental evidence.
Keywords: tensors, borax, tincalconite, nuclear, magnetic, resonance, ferroelectric, lithium